Interfaces da educação especial e ensino superior : processos constitutivos de acesso e permanência no Brasil e no México - Souza, Caroline de Andrade (2018)
This paper presents results from investigation performed on the process of handicapped people’s inclusion in upper education institutions, more precisely, in UFES (Federal University of Espirito Santo State, located in Vitória- ES, Brazil and in UV (Veracruzana University) in Xalapa, Mexico. This research is based on the compared study which has allowed the investigation of two realities, considering two singularities, this way providing a greater comprehension on the complexity of this field of investigation. This study had as a purpose to analyze the possibility of access and permanence of target student from special education in upper education. Methodologically, this work was supported by official documents which express the policy of access and permanence of these students in the two universities. There was systematization of data relating to the number of students, according to the type of disability, enrolled in on-site graduation courses provided by the universities. Through these interviews, one has appealed to figurations that make it possible the access and permanence of this public into the context of these two places, by the aid of the discourse of professionals who work in different departments of these institutions as well as the discourse of the students. The work had The Figurational Sociology by Norbert Elias as theoretical guide. Having as support the contributions of this author, it was pertinent to work with the social process, figuration and interdependence concepts. These concepts stimulated thoughts on how the process of handicapped people’s inclusion has been arranged over the history. The results of the research pointed out the dialogues that are established between the figures of the university for the permanence of students targeted to special education. The constructions and articulations of the actions to the specific policies for the access and permanence of people with disabilities add to this social process, as well as actions limited by lack or scarcity of public budget. It was clear that the presence of the target audience of Special Education has been aimed at changes and the two universities are looking for ways to include all, that dialogues should be established between departments, collegiate or sectors of campuses that could collaborate for attitudinal, structural changes. The concerns of the individuals involved in these processes have also been highlighted and much remains to be done and this is still under construction.